EMPIRICAL ANALYSIS OF THE EFFECT OF CAPITAL ADEQUACY RATIO, NON-PERFORMING LOAN, AND RETURN ON ASSET ON FINANCIAL SUSTAINABILITY OF ENERGY SECTOR COMPANIES GOING PUBLIC IN 2022-2024 - Nurhaliza Ahmad; Gunistiyo, Gunistiyo; Mohammad Arridho Nur Amin (Ikatan Dosen Menulis, 2025)
123